Fidélité et politique - Jean-Pierre Dedieu (Mélanges de la Casa de Velázquez, 2004)
The notion of fidelity is sometimes implicit and sometimes explicit in the study of relations between the Spanish monarchy and the towns. To delimit the meaning of the word fidelity more exactly requires a detour through lexical terrain as well as close attention to the objects of fidelity (a sovereign, a family, a society, a province, a State). In this process there are two poles that define the type of relationship that brings them together and that organises the political, legal and moral space in which fidelity shifts from one to the other, assured by the respect that the upper pole owes to the lower pole. This is what makes revolt possible, but also negotiation and interchange.